The Role of Abiotic Soil Parameters as a Factor in the Success of Invasive Plant Species - Wieger Wamelink; H.F. van Dobben; P. W. Goedhart; L.M. Jones-Walters (Ital Publication, 2018)
Plant species dispersal has been strongly enhanced by human activities. Introduced species have to cope with indigenous species and local conditions. They may avoid indigenous species by occupying new (abiotic) territory. Once a species is established it may become a pest, and may seriously threaten other species and ecosystems.In this paper we focus on invasive plant species of the Dutch flora. We make two comparisons: (1) Dutch neophytes (i.e. arrived in The Netherlands after 1825) vs. indigenous Dutch flora; and (2) species of the Dutch flora that have become invasive outside Europe vs. non-invasive species of the Dutch flora. We hypothesize that at least part of the success of the invasive or neophyte species is due to their ability to grow under a wider range of abiotic soil circumstances than other species. We regard an invasive species as successful if it is able to disperse from the introduction site(s) and remain present in the invaded vegetation.For ten out of the sixteen abiotic factors there is a wider range for the neophytes: chlorine, potassium, mean highest and lowest groundwater level, phosphorus (and total content) and pH H2O.We hypothesized that part of the success of invasive species may be the adaptation to a variety of abiotic soil parameters. This is indeed the case for a number of the examined parameters, mostly related to nutrient availability and soil pH. This indicates that the success of invasive species is at least partly caused by their ability to grow under a wide range of nutrient availability and soil pH. Their success may therefore be stimulated by the increasing pollution of natural areas by excessive nitrogen.